2008
DOI: 10.1063/1.2830995
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microwave absorption in Ni/polyaniline nanocomposites by dual dielectric relaxations

Abstract: Ni/polyaniline (PANi) nanocomposites were prepared by chemical polymerization, and electromagnetic characteristics were then studied at 2–18GHz. The permittivity of the Ni/PANi nanocomposite presents dual dielectric relaxations with increasing content of PANi to over 15.6wt%, which is ascribed to a cooperative consequence of the core/shell interfaces and the dielectric PANi shells. Additionally, the permeability presents a strong natural resonance around 2–8GHz, which is dominant among microwave magnetic loss.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
180
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(189 citation statements)
references
References 8 publications
8
180
1
Order By: Relevance
“…For the imaginary part of the permittivity ε″, it can be seen in Fig. 10 (b) that ε″ of the samples increases with the nanospheres is mainly due to natural resonance of the Fe 3 O 4 nanoparticles [31,32]. It is believed that natural resonance results in strong magnetic loss, implying enhanced microwave absorption by the HPAP-Fe 3 O 4 nanospheres as EM energy is converted into heat energy [33].…”
Section: Microwave Absorption Propertiesmentioning
confidence: 99%
“…For the imaginary part of the permittivity ε″, it can be seen in Fig. 10 (b) that ε″ of the samples increases with the nanospheres is mainly due to natural resonance of the Fe 3 O 4 nanoparticles [31,32]. It is believed that natural resonance results in strong magnetic loss, implying enhanced microwave absorption by the HPAP-Fe 3 O 4 nanospheres as EM energy is converted into heat energy [33].…”
Section: Microwave Absorption Propertiesmentioning
confidence: 99%
“…The resonant frequencies of ε in the current frequency range are 6.0 and 15.8 GHz, respectively. Dong et al reported that the plot of ε' versus ε'' would be a single semicircle, which was usually defined as the Cole-Cole semicircle 26 . It is worthy to note that the composite present a clear segment of two semicircles in Figure 3(c), suggesting the existence of dual dielectric relaxation processes, while each semicircle corresponds to a Debye dipolar relaxation 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Dong et al reported that the plot of ε' versus ε'' would be a single semicircle, which was usually defined as the Cole-Cole semicircle 26 . It is worthy to note that the composite present a clear segment of two semicircles in Figure 3(c), suggesting the existence of dual dielectric relaxation processes, while each semicircle corresponds to a Debye dipolar relaxation 26 . During the activation of an EM-wave, a redistribution process of the charges occurs periodically between the FeNi cores and the SnO shells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various potential candidates for EM wave absorbers, the one in the form of magnetic nanoparticles core/ dielectric shell-structured nanocapsules, such as Ni/ZnO, FeNi 3 /SiO 2 , Ni/PANI, Ni/C, and Ni/Ni 2 O 3 nanocapsules, has been of particular interest in recent years owing to its tailorable properties in conjunction with smaller sizes and weights [6][7][8][9][10] . An essence of determining the EM wave absorbing properties of the nanocapsules is to obtain a balance between the permeability of the magnetic nanoparticle cores with the permittivity of the dielectric shells 11 .…”
Section: Introductionmentioning
confidence: 99%